Performance assessment of a rotary active magnetic regenerator prototype using gadolinium. (5th March 2022) - Masche, M.; Liang, J.; Engelbrecht, K.; Bahl, C.R.H.
Highlights: The cooling performance of a multi-bed AMR device with gadolinium is presented. A cooling power of 818 W with a COP of 4.2 was achieved over a 10 K span. The device can establish a 16.6 K span starting from room temperature in 25 min. Active valve control can increase cooling power and COP by more than 70%. A maximum second-law efficiency of 39.2% was obtained at a span of 7.3 K. Abstract: We present the experimental results for a rotary magnetocaloric prototype that uses the concept of active magnetic regeneration, presenting an alternative to conventional vapor compression cooling systems. Thirteen packed-bed regenerators subjected to a rotating two-pole permanent magnet with a maximum magnetic field of 1.44 T are implemented. It is the first performance assessment of the prototype with gadolinium spheres as the magnetocaloric refrigerant and water mixed with commercial ethylene glycol as the heat transfer fluid. The importance of various operating parameters, such as fluid flow rate, cycle frequency, cold and hot reservoir temperatures, and blow fraction on the system performance is reported. The cycle frequency and utilization factor ranged from 0.5 to 1.7 Hz and 0.25 to 0.50, respectively. Operating near room temperature and employing 3.83 kg of gadolinium, the device produced cooling powers exceeding 800 W at a coefficient of performance of 4 or higher over a temperature span of above 10 K at 1.4 Hz. It was also shown that variations in the flow resistance between the beds could significantly limit the system performance, and a method to correct those is presented. The performance metrics presented here compare well with those of currently existing magnetocaloric devices. Such a prototype could achieve efficiencies as high as conventional vapor compression systems without the use of refrigerants that have high global warming potential.